Relationship between Parenting and Cognitive Schemas in a Group of Male Adult Offenders - Pellerone, Monica; Craparo, Giuseppe; Tornabuoni, Ylenia (Frontiers in Psychology, 2016)
This work analyzes the correlation of retrospective ratings on parental binding with cognitive patterns in the inmates for property crimes. The participant group comprehended 248 adults men, including 130 marked out as offenders (the experimental group), aged between 19 and 70, currently serving sentences in the Cavadonna prison in Siracusa, and 118 marked out as non-offenders (the control group), aged between 20 and 70, living in Siracusa (Sicily). The instruments used were the Parental Bonding Instrument (PBI), and the Young Schema Questionnaire-3 (YSQ). The preliminary analysis showed an high percentage of offenders who experienced an affectionate constraint parenting. Offenders scored significantly higher than the non-offenders on the level of paternal control and the YSQ subscales. The study underlines the influence of maternal care on most of the cognitive schemas, and the role of father’s control on the tendency to social isolation and defectiveness in the offenders.